Family planning for women with severe mental illness in rural Ethiopia: a qualitative study - Tigist Zerihun; Katherine Sorsdahl; Charlotte Hanlon (BMC, 2021)
Plain language summary Family planning is a crucial issue for all women of reproductive age, but in women with severe mental illnesses (SMI), including conditions like schizophrenia, bipolar disorder and severe depression, there may be particular challenges and concerns. Very little is known about the unmet family planning needs of women with SMI who live in low- and middle-income countries. In this study, we explored the family planning experiences, unmet needs and preferences of women with SMI who live in a rural area of Ethiopia. We identified women with SMI who were taking part in a community study asking about their use of family planning. We selected 16 women with low and high use of family planning to interview in depth. The study women spoke of how having a mental illness drastically affected their intimate relationships and sexual life. Although the women felt that family planning was important, they had limited knowledge of family planning generally and a lack of understanding of the specific issues that mental illness might have on family planning choices. None of the women had received any recommendations to use family planning services while accessing mental health care services. The participants identified ways in which primary care-based mental health services could better meet their family planning needs. We concluded that it is important to focus on empowerment of women with SMI in this rural Ethiopian community, making sure that they have access to the kind of information and services that they need for family planning.